Historic development of regional economic integration and its impact on Singapore. - Lim, Wee Lee. (2008)
This paper attempts to trace the historical development of regional economic integration and whether bilateral agreements like Free Trade Agreements will really help to accelerate and maintain Singapore’s growth momentum and review the pros and cons in the regional integration process, the economic impact of the FTAs to Singapore, and the challenges that Singapore is facing in her endeavor of this pursue.